Influence of Residential Internet Access and Patented Innovation on U.S. Non-store Retail Industries’ Employment - Khan, Abdullah (Advances in Social Sciences Research Journal, 2023)
This paper studies employment trends of the U.S. nonstore retail industries at multi-jurisdictional levels (States, Census Regions, Census Division, and the nation) for years 2001 through 2021. The nonstore retail industry is a growing subsector of the overall retail industry. With no or skeletal ‘brick- and-mortar presence’, nonstore retailers are poised for leveraging information and communication technologies and innovations from the inception of their business operations. With the need for scaling up in the backdrop of limited or zero ‘on-site’ customer-interactions, the nonstore retailers are inclined to find novel ways to interact and transact with existing and prospective customers. As more and more brick-and-mortar stores begin to offer electronic shopping opportunities from their web-based stores, traditional nonstore retailers face steeper competition. Utilizing panel data regressions this paper explores marginal impacts of residential internet access, patented innovations, and other fiscal and macroeconomic variables on nonstore retail industry (NAICS Code 454). The regression results suggest that residential internet access is a positive influence on both nonstore retail employment and number of nonstore retail entities. The results also suggest that utility patents and design patents are positive factors for growth of nonstore retail industry’s employment and business entities.